PENGARUH TINGKAT PENDIDIKAN, PELATIHAN DAN MOTIVASI TERHADAP PENINGKATAN KUALITAS PELAYANAN PEGAWAI DI RSUD PADJONGA DG. NGALLE KABUPATEN TAKALAR - Azizah, Nurul; Salim, Agus; Khalid, Idham (COMPETITIVENESS, 2020)
Human resources development of the State Civil Apparatus (ASN) through education and training to form a professional apparatus. In order to be able to carry out its duties and functions so that services to the community can be qualified. The importance of education and training programs in the government apparatus is realized education through school lines, both public education and vocational education. This study aims to find out and analyze the influence of education level, training and motivation on improving the quality of employee services at Padjonga Daeng Ngalle Hospital Takalar Regency. This type of research is quantitative with explanatory research approach. The population in this study was employees of Padjonga Daeng Ngalle Hospital Takalar Regency. Sampling techniques using simple random sampling distributed to 269 respondents. The analytical method used in this study is multiple linear analysis.The results of this study showed that education has an insignificant positive influence on improving the quality of service; training has a significant positive influence on improving the quality of service; motivation has a significant positive influence on improving the quality of service; training has a dominant effect on the quality of service. Different medical and non-medical sample tests of four direct variables hypothesized only significantly different medical and non-medical motivations. This shows that the better the training and motivation of employees' work, the better the quality of service.